Synovitis detected on magnetic resonance imaging and its relation to pain and cartilage loss in knee osteoarthritis. Issue 12 (9th May 2007) - Hill, Catherine L; Hunter, David J; Niu, Jingbo; Clancy, Margaret; Guermazi, Ali; Genant, Harry; Gale, Daniel; Grainger, Andrew; Conaghan, Philip; Felson, David T
Abstract : Objective: To examine the relationship between longitudinal fluctuations in synovitis with change in pain and cartilage in knee osteoarthritis. Methods: Study subjects were patients 45 years of age and older with symptomatic knee osteoarthritis from the Boston Osteoarthritis of the Knee Study. Baseline and follow-up assessments at 15 and 30 months included knee magnetic resonance imaging (MRI), BMI and pain assessment (VAS) over the last week. Synovitis was scored at 3 locations (infrapatellar fat pad, suprapatellar and intercondylar regions) using a semiquantitative scale (0–3) at all 3 time points on MRI. Scores at each site were added to give a summary synovitis score (0–9). Results: We assessed 270 subjects whose mean (SD) age was 66.7 (9.2) years, BMI 31.5 (5.7) kg/m 2 ; 42% were female. There was no correlation of baseline synovitis with baseline pain score (r = 0.09, p = 0.17). The change in summary synovitis score was correlated with the change in pain (r = 0.21, p = 0.0003). An increase of one unit in summary synovitis score resulted in a 3.15-mm increase in VAS pain score (0–100 scale). Effusion change was not associated with pain change. Of the 3 locations for synovitis, changes in the infrapatellar fat pad were most strongly related to pain change. Despite cartilage loss occurring in over 50% of knees, synovitis was not associated with cartilage loss in either tibiofemoral or patellofemoral compartment. Conclusions: Change in synovitis was correlated with change in knee pain, but not loss of cartilage. Treatment of pain in knee osteoarthritis (OA) needs to consider treatment of synovitis.